VALIDASI ATLAS LIKEN DI KOTA BLITAR - Sofiyana, Marinda Sari (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to determine the feasibility of a Liken Atlas in Blitar City. Eligibility is obtained from material and media validation. This research approach is descriptive qualitative. Data collection was obtained using a validation questionnaire from material experts and media experts. The material expert validation got a percentage score of 95.63, while the media expert validation got a percentage score of 89.60. The two validation scores indicate that the Liken Atlas in Blitar City is very feasible.